Review essay: Shuttered experiences and revolution; A. Agathangelou and N. Soguk, (eds), Arab Revolutions and World Transformations - Bartsidis, Michalis; Tsibiridou, Fotini (Historein, 2014)
This review essay involves a critical presentation and reflection of the volume edited by Anna Agathangelou and Nerzat Soguk entitled Arab Revolutions and World Transformations (London: Routledge, 2013). This volume contributes to the enrichment of the problematic regarding the Arab uprisings and opens up a discussion on three basic issues: firstly, revolution within the framework of postcolonial critique; secondly, the encounters between the local and the global; and lastly on the impact of social poetics and aesthetics of people as agents, beyond dominant orientalised discourses and representations of otherness. Under the lens of political anthropology and philosophy, this review essay introduces to these critical approaches an additional focus, that of the concept of “dignity”. Its ethical dimension should remind us of the importance of affect on the building of the universally posed political questions concerning democracy, revolution, social movements, citizenship and civic virtue.